Structure-activity relationships in carbohydrates revealed by their hydration. - Maugeri, L; Busch, S; McLain, S; Pardo, L; Bruni, F; Ricci, M (Elsevier, 2016)
One of the more intriguing aspects of carbohydrate chemistry is that despite having very similar molecular structures, sugars have very different properties. For instance, there is a sensible difference in sweet taste between glucose and trehalose, even though trehalose is a disaccharide comprised of two glucose units, suggesting a different ability of these two carbohydrates to bind to sweet receptors. Here we have looked at the hydration of specific sites and at the three-dimensional configuration of water molecules around three carbohydrates (glucose, cellobiose, and trehalose), combining neutron diffraction data with computer modeling. Results indicate that identical chemical groups can have radically different hydration patterns depending on their location on a given molecule. These differences can be linked with the specific activity of glucose, cellobiose, and trehalose as a sweet substance, as building block of cellulose fiber, and as a bioprotective agent, respectively.